Comparative Analysis of Tools for Modelling Business Processes of Organization Management - Lomakin, V.; P. Putivtseva, N.; V. Zaitseva, T.; P. Pusnaya, O.; M. Zaitsev, I. (International Journal of Engineering and Technology, 2018)
The article presents the result of a comparative analysis of software tools that allow modelling business processes of organizations. For comparison, those software tools for modelling business processes that support the BPMN methodology were chosen. As a method of conducting a comparative approach, a comprehensive approach was used, including the use of the hierarchy analysis method, which allows us to find the weight of comparison criteria that were identified on the basis of the analysis of literature sources, Internet resources, and features of the functionality of the business process modelling tools selected for comparison , and a formalized approach that allows calculating the priorities of alternative software modelling tools depending on their grades by dedicated channels on each criterion.Â Â